2019
DOI: 10.15171/jnp.2019.44
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of ACE gene I/D polymorphism with the risk of diabetic kidney disease; a meta-analysis

Abstract: Introduction: Diabetic nephropathy (DN) is a progressive renal disease characterized by persistent albuminuria that leads to end-stage renal disease in both type 1 diabetes (T1DM) and type 2 diabetes (T2DM) patients. The renin-angiotensin-aldosterone system (RAAS) plays a major role in the onset and progression of DN. Objectives: The present meta-analysis is intended to synthesize evidence on the association between ACE gene insertion and deletion (ACE I/D) polymorphism and the risk of DN. Methods: PubMed, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Controlling glycemic response is important to improve clinical outcomes and quality of life especially in patients with metabolic disorders (Lakkakula, Khare, Verma, & Pattnaik, 2019; Livesey, Taylor, Hulshof, & Howlett, 2008; Ramzan et al, 2019). Failure to achieve glycemic response goals is associated with serious consequences and substantial costs (Goel, Grover, Sharma, & Bae, 2018; Livesey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Controlling glycemic response is important to improve clinical outcomes and quality of life especially in patients with metabolic disorders (Lakkakula, Khare, Verma, & Pattnaik, 2019; Livesey, Taylor, Hulshof, & Howlett, 2008; Ramzan et al, 2019). Failure to achieve glycemic response goals is associated with serious consequences and substantial costs (Goel, Grover, Sharma, & Bae, 2018; Livesey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence has shown that RAAS plays an essential role in the development and progression of DN (10). Recently, some genetic variants such as angiotensin-converting enzyme (ACE) I/D polymorphism, angiotensin II type 1 receptor (AT1R) A1166C (rs5186) gene polymorphism and AGT M235T (rs699) in the RAAS pathway have been significantly associated with the risk of DN (11,12). AGT is a vital component of level II angiotensin, which is a major component of the RAAS.…”
Section: Introductionmentioning
confidence: 99%